Water beetles from the Bokkeveld Plateau: a semi-arid hotspot of freshwater biodiversity in the Northern Cape of South Africa - Bilton, David T. (Zootaxa, 2017)
The Bokkeveld Plateau in the Northern Cape of South Africa supports a complex transition zone between the fynbos and succulent karoo biomes on the margins of Namaqualand. A combination of regular winter rainfall, geology and strong rainfall gradients mean that the region supports a diverse and highly endemic flora. Recent sampling of aquatic beetles in the Bokkeveld demonstrates that this region also has a diverse freshwater fauna, including a number of apparent endemics. Five new species of Hydraenidae (Pterosthetops chrysomallus sp. nov., Parastetops porcellus sp. nov., Mesoceration castaneum sp. nov., M. chasmum sp. nov., and M. sabulosum sp. nov.) are described from the Bokkeveld, and new records provided for 68 other water beetle taxa recorded during recent fieldwork in the region, 28 of which are new to Northern Cape Province. Most of the newly described species are relatively common in the region, suggesting that additional taxa may remain undetected in this apparent hotspot of freshwater diversity.